EFEK RICARDIAN EQUIVALENCE HYPOTHESIS TERHADAP PEREKONOMIAN DI INDONESIA TAHUN 1997-2021 - novi widyaningrum (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2022)
The purpose of this study is to examine how much influence the effect of the Ricardian Equivalence Hypothesis has on the economy in Indonesia in 1997-2021. Secondary data was used in this study with the Error Correction Model (ECM) data analysis method. The results of this study indicate that in the short term it is only significantly influenced by the government spending variable (GOV). Deficit variable (DEF), foreign debt (ULN), exchange rate (KURS) have no significant effect. In the long run, variables that have a significant effect on economic growth are DEF and foreign debt. The exchange rate variable and GOV have no significant effect.